A paper-based potentiometric sensing platform based on molecularly imprinted nanobeads for determination of bisphenol A. Issue 31 (1st August 2018) - Kamel, Ayman H.; Jiang, Xiaojing; Li, Pengjuan; Liang, Rongning
Abstract : For the first time, a simple, low-cost paper-based platform based on uniform-sized MIP nanobeads for potentiometric sensing of bisphenol A is reported. Abstract : Currently, the electrode substrates of solid-contact potentiometric sensors for bisphenol A (BPA) are usually expensive glassy carbon, gold or platinum. This poses serious limits to the wide use of these sensors, especially in less developed countries. Herein, we present for the first time a simple and ultra-low-cost, disposable paper-based potentiometric sensor for determination of neutral BPA. Uniform-sized molecularly imprinted nanobeads are utilized as a recognition receptor to provide a higher affinity for BPA since they have larger binding capability and can be well dispersed in the polymeric membrane potentiometric sensor. Commercially available chromatography paper is used as the electrode substrate to build the sensor. It has been found that the proposed paper sensor exhibits similar analytical performance to the classical glassy carbon-based sensor. The present sensor shows a linear anionic potential response over the concentration range from 0.5 to 13 μM with a detection limit of 0.15 μM and exhibits good selectivity over other phenols. The proposed sensing platform has been successfully applied to determination of BPA released from real plastic samples.